The Influence Of International Brand Image Toward Guest's Decision To Stay At The Four Star Hotel In Lampung - Dina mayasari soewoyo; Handono W Widodo (Journal FAME: Journal Food and Beverage, Product and Services, Accomodation Industry, Entertainment Services, 2021)
This survey research using the quantitative method was carried out during the Covid-19 pandemic, from May to August 2020 at the 4-star hotel in Lampung Province, Indonesia. The purpose of this study was to determine the influence of the independent variable, namely the image of the international hotel brand toward the dependent variable of guests' decisions to stay at the hotel. Primary data of the study were obtained from the results of distributing questionnaires which were carried out directly to 60 guests who were staying, as research samples and measured using a Likert scale of 1 - 4. Apart from distributing questionnaires, research data collection was also gained through observation, documentation, and literature review. All data collected were then grouped, reduced, tabulated and processed, analyzed descriptively, and statistically, in accordance with the context of the problem being studied using the SPSS 22.0 software tool.Based on the simple linear regression analysis technique T-test (partial), R test and R square test, it was found that the value of T count (9,048) was greater than the T table (1,671), with a significance value of 0 or below the significance limit of 0.05. Both variables have a correlation coefficient of 0.765 and a coefficient of determination of 0.585. So it can be concluded that the international hotel brand image has a strong, positive, and significant influence on guest decisions to stay at the 4-star hotel in Lampung, with an effect of 58.5% while the rest, namely 41.5%, is influenced by other variables not examined in this study.